eTutor4U platform: acquiring knowledge and skills with the help of great tutors - Safari, Muhammad Shukri; Abdullah, Muhammad Badiuzzaman; Ahmad Dahlan, Abdul Rahman (IEEE Explore, 2018)
The objective of this paper is to propose an online platform that linking between students and tutors through mobile and web-based named as “eTutor4U”. With the increasing trend of on-demand tutoring and educational technology this platform will give benefit to all generation’s. The service not only offers to students but it also applicable for workers because this platform is not only specified in educational area, but it also provides tutor that can share skills. “eTutor4U” is a conceptual business model which provides a flexible solution to customer that gives them the freedom to put a price in getting good tutors. Literature Review, strategy canvas, value proposition design (VPC), environmental map, future work and business plan has been used as the methodologies for this paper.